The DEVELOPMENT OF INTERACTIVE E-MODULES ASSISTED WITH CANVA AND PROFESSIONAL FLIP PDF ON OPPORTUNITY MATERIALS - Virda Putri Novita Wulandari; Dian Devita Yohanie; Darsono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
This research aims to determine the results of the validity and practicality of developing interactive e-modules assisted by Canva and Flip PDF Professional on Opportunity material for class X SMA. The type of research used is Research and Development (R&D) with the ADDIE development model which includes five stages: analysis, design, development, implementation, and evaluation. The research results show that the e-module product developed is included in the